Supramolecular Glyco‐nanoparticles Toward Immunological Applications. Issue 45 (12th October 2015) - Lin, Mingchang; Zhang, Yufei; Chen, Guosong; Jiang, Ming
Abstract : Glyco‐mimicking nanoparticles (glyco‐NPs) with Förster resonance energy transfer (FRET) donor and acceptor groups formed via dynamic covalent bond of benzoboroxole and sugar from two complementary polymers are prepared. The glyco‐NPs are proved to be quite stable under physiological conditions but sensitive to pH. So the glyco‐NPs can be internalized by dendritic cells with integrity and nontoxicity and then dissociate within the acidic organelles. This particle dissociation is directly observed and visualized in vitro, for the first time via the FRET measurements and fluorescent microscopy. This feature makes controlled release of drug or protein by glyco‐NPs possible, i.e., when model antigen Ovalbumin is loaded in the glyco‐NPs, the released Ovalbumin in dendritic cells stimulates T cells more efficiently than the free Ovalbumin itself as a result of the enhanced antigen processing and presentation. Thus, the results enlighten a bright future of the glyco‐NPs in immunotherapy. Abstract : A self‐assembled glyco‐nanoparticle is reported which is stable to temperature, sugar, and oxidants but very sensitive to pH. Moreover, its dissociation in vitro is visualized and localized for the first time by Förster resonance energy transfer. Antigen release and subsequent T‐cell activation are also demonstrated.